OPTIMASI PEMBENTUKAN NANOPARTIKEL PERAK DENGAN BIOREDUKTOR DARI EKSTRAK DAUN TAHONGAI ( Kleinhovia hospita Linn.) - -, Rahayuningsih; Hindryawati, Noor; Syaima, Husna (Jurusan Kimia FMIPA UNMUL, 2024)
The synthesis of Silver Nanoparticles was carried out by bottom-up method by reducing Ag+ ions to Ag0 using Tahongai leaves (Kleinhovia hospital Linn) which contain secondary metabolites such as alkaloids, flavanoids and phenolics as bioreductors that reduce AgNO3 solution as a precursor. The purpose of this study was to determine whether tahongai leaves can be used as a bioreductor in the synthesis of silver nanoparticles. The concentration variation of tahongai leaf extract bioreductor was 25 %; 50 %; and 75 %. Changes in silver nanoparticles can be marked by changes in the color of the solution and by UV-Vis Spectrophotometer absorption. The results of this study showed a change in color of AgNO3 solution from clear to brownish yellow which indicates the formation of silver nanoparticles, and through UV-Vis Spectrophotometer analysis showed absorption at wavelengths of 420 to 430 which indicates relatively stable nanoparticles so it can be concluded that tahongai leaf extract can be used as a bioreductor for the synthesis of silver nanoparticles.